The Effect of Giving Extract of Lannea Coromandelica (Lannea coromandelica (Houttuyn) Merrill) Leaf to Decrease the Blood Sugar Level of Mice (Mus musculus) - Moh. Husaini; Supriadi Supriadi; Minarni R. Jura (Universitas Tadulako, 2019)
The Indian ash tree leaf (Lannea coromandelica (Houttuyn) Merrill) contains natural ingredients that can reduce blood glucose levels. This study aimed to determine the concentration of the Indian ash tree leaf extract which is the most effective to reduce blood sugar levels of mice. The leaf sample of the Indian ash tree plant was obtained from Talise sub-district, Mantikulore district, Palu, Central Sulawesi. The preparation of the extract was conducted by the maceration method. The animal testing used were 20 male mice that were induced by EDTA (ethylene diamine tetraacetic acid). Mice were divided into 5 groups as random with different treatments. Treatments I, II, and III were given an extract of 10, 20, and 40%, respectively, treatment IV was given Na-CMC as a negative control (-), and treatment V was given glibenclamide suspension as a positive control (+). The data obtained were analyzed by statistical analysis of variance analysis (ANOVA) and were continued by the Duncan test. The results showed that the Indian ash tree leaf extract can reduce the blood sugar levels of mice. The mean decreased blood glucose level at treatment I was 40.00 mg/dL, treatment II was 47.75 mg/dL, treatment III was 54.75 mg/dL, treatment IV was 1.75 mg/dL, and treatment V was 49.00 mg/dL. The conclusion of this research was that the Indian ash tree leaf extract could reduce the blood sugar level of mice with an effective concentration of 20% with α = 0.05.